2015
DOI: 10.1097/ccm.0000000000000949
|View full text |Cite
|
Sign up to set email alerts
|

The Selective Sirtuin 1 Activator SRT2104 Reduces Endotoxin-Induced Cytokine Release and Coagulation Activation in Humans*

Abstract: This is the first human study to demonstrate biological anti-inflammatory and anticoagulant responses consistent with the activation of sirtuin 1 by a small molecule.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 54 publications
(40 citation statements)
references
References 10 publications
0
39
1
Order By: Relevance
“…This appears to be linked to changes in bioenergetics that occur in tolerized cells [52]. Treatment with a SIRT1 activator reduces production of TNF-a and IL-12p40 in response to LPS injection in mice [116] and IL-6 and IL-8 after LPS injection in humans [117], supporting these results.…”
Section: Metabolic Changes During Lps Tolerancementioning
confidence: 63%
“…This appears to be linked to changes in bioenergetics that occur in tolerized cells [52]. Treatment with a SIRT1 activator reduces production of TNF-a and IL-12p40 in response to LPS injection in mice [116] and IL-6 and IL-8 after LPS injection in humans [117], supporting these results.…”
Section: Metabolic Changes During Lps Tolerancementioning
confidence: 63%
“…Both SIRT1 activators have been shown to improve healthspan in mice, reducing inflammation and protecting from neurodegeneration (Hubbard and Sinclair, 2014). According to one clinical study, SRT2104 can reduce the serum levels of interleukin-6 and C-reactive protein induced by intravenous injection of lipopolysaccharide (van der Meer et al, 2015). Additional data on SRT2104 effects on human health will likely be reported in the near future.…”
Section: Resveratrol and Other Sirt1 Activatorsmentioning
confidence: 99%
“…SIRT1 deacetylates P53 and thereby inactivates P53-triggered transcription of its downstream genes (Vaziri et al 2001, Cheng et al 2003, Kim et al 2007. Although P53 was reported to participate in the pathogenesis of DM and a few of its complications (Deshpande et al 2013, Tang et al 2014, Kung & Murphy 2016, Li et al 2016, Su et al 2017, little was known for its role in diabetic vasculopathy. The pioneer work by Orimo and coworkers showed that high glucose (HG) resulted in hyperacetylation of P53 in HUVECs, the effect of which led to endothelial dysfunction (Orimo et al 2009).…”
Section: Journal Of Endocrinologymentioning
confidence: 99%